2021
DOI: 10.1111/cod.13837
|View full text |Cite
|
Sign up to set email alerts
|

Should methyldibromo glutaronitrile continue to be used in the European baseline Series? A REIDAC national cross‐sectional study

Abstract: Background Methyldibromo glutaronitrile (MDBGN) was one of the most frequent and relevant allergens found in patch testing at the beginning of this century. In 2008, this preservative was banned from cosmetics in Europe and ever since the prevalence of contact allergy to MDBGN has progressively decreased. Despite that gradual decline, MDBGN is still patch‐tested in most baseline series. This study assessed the frequency of MDBGN sensitization, epidemiological characteristics of allergic patients, and the relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…The results of several epidemiological European studies including ours [4][5][6] showed a declining trend in the frequency of contact allergy to MDBGN in Europe since its banning from cosmetics, indirectly reflecting a good compliance with the regulatory guidelines by manufacturers. This declining trend was especially evident when we stratified by age groups, 2,6 with the younger individuals significantly showing the lower frequency of positive tests. Accordingly, we only found one positive test involving one patient out of 343 tested (all under the age of 20 years).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The results of several epidemiological European studies including ours [4][5][6] showed a declining trend in the frequency of contact allergy to MDBGN in Europe since its banning from cosmetics, indirectly reflecting a good compliance with the regulatory guidelines by manufacturers. This declining trend was especially evident when we stratified by age groups, 2,6 with the younger individuals significantly showing the lower frequency of positive tests. Accordingly, we only found one positive test involving one patient out of 343 tested (all under the age of 20 years).…”
mentioning
confidence: 89%
“…To the Editor, We would like to thank Lidén and White for their "Comment on MDBGN/DBDCB, the European baseline series, and EU legislation" 1 regarding our publication 2 and their thorough and accurate review about legislation concerning methyldibromo glutaronitrile (MDBGN) in Europe. We are aware that the information about the current status of legislation was not provided in our article; however, such a type of review was beyond the scope of our research.…”
mentioning
confidence: 99%
“…Some authors, when unable to confirm current relevance based on label information, have suggested that most reactions are irritant, doubtful, false-positive, or of only past relevance. 1,[3][4][5][6][7] Some authors have even recently suggested that MDBGN/ DBDCB be deleted from the European baseline series, 1,3,4 and it has been decided by the American Contact Dermatitis Society to that the substance be removed from its core allergen series, 6 despite relatively high prevalence of contact allergy. 1,[8][9][10] We consider that omitting the substance from the baseline series, instead of tracking exposure more efficiently, will harm surveillance and prevention of skin sensitization and allergic contact dermatitis.…”
Section: Patch Testing With Mdbgn/dbdcbmentioning
confidence: 99%
“…In response to "Comment on MDBGN/DBDCB, the European baseline series, and EU legislation", 1 replied to our Letter to the Editor 2 regarding their recent paper. 3 In their reply, 1 Mercader-García et al avoid the key points of concern in our Letter to the Editor 2 :1. We do not think and have not suggested that there is currently widespread or uncontrolled use of methyldibromo glutaronitrileHowever, we are concerned that use, sensitization, and elicitation will increase owing to the ongoing global campaign by LANXESS marketing MDBGN/DBDCB.…”
mentioning
confidence: 93%
“…In response to "Comment on MDBGN/DBDCB, the European baseline series, and EU legislation", 1 replied to our Letter to the Editor 2 regarding their recent paper. 3 In their reply, 1 Mercader-García et al avoid the key points of concern in our Letter to the Editor 2 :…”
mentioning
confidence: 94%